A review of the dog snapper (Lutjanus jocu) along the Brazilian Province: Distributional records, ecology, fisheries and conservation. (1st April 2022) - Menezes, Rafael; Giglio, Vinicius J.; Albuquerque, Cristiano Q.; Rosa, Ricardo S.
Abstract: The dog snapper, Lutjanus jocu, is a commercially exploited fish throughout the Brazilian Province (BP) and has been facing overexploitation. However, there are no systematized data on the species to date, which hinders management strategies for mitigating this scenario. In this review, we gathered the existing literature information on L. jocu along the BP, focusing on distributional records, ecology, fisheries and conservation. A total of 253 records were attained in 212 studies, with the highest number found on the northeastern Brazilian coast. The species occurred in a multitude of habitats, such as estuaries, tidepools and reef systems, and was caught by a variety of fishing gear. We evidenced that ecological and fishery information on L. jocu is geographically biased in the BP, being prevalent on the northeastern coast and scarce or even absent in all other regions. To guide a L. jocu fisheries management in the BP, we propose a low-cost framework containing three major initiatives: i) participatory mapping of fishing and aggregation grounds, ii) slot size limit regulation backed by eco-labeling, and iii) citizen science-based monitoring. Efforts to establish dog snapper fisheries management and monitoring should be urgently implemented to avoid the collapse of the stock in the BP. Highlights: The dog snapper is a commercially exploited fish along the Brazilian Province (BP). This review covered 253 records in 212 studies on the dog snapper in the BP. The species occurred in a multitude of habitats and was caught by multiple fishing gears. Ecological and fisheries data are prevalent in the northeast and scarce in all other regions. A fisheries management framework is proposed to mitigate the overexploitation trend.